Mesoporous silica nanoparticles as carriers of active agents for smart anticorrosive organic coatings: a critical review. Issue 20 (13th May 2021) - Olivieri, Federico; Castaldo, Rachele; Cocca, Mariacristina; Gentile, Gennaro; Lavorgna, Marino
Abstract : Mesoporous silica nanoparticles with properly designed textural properties and tailored release of corrosion inhibitors are highly efficient smart carriers for advanced anticorrosive nanocomposite coatings. Abstract : Mesoporous silica nanoparticles (MSN) have attracted increasing interest for their applicability as smart nanocarriers of corrosion inhibitors, due to their porous structure, resistance to main corrosive environments and good compatibility with polymer coatings. In this review, the main synthetic routes to obtain MSN with tailored textural properties, the design of different loading and stimuli-induced release strategies, the development of advanced organic nanocomposite coatings with MSN and the validation of their anticorrosive performances are reviewed and compared. Through a critical analysis of the literature, the most promising research trends and perspectives to exploit the highly interesting properties of MSN in advanced organic coatings are proposed.